Preparation method and application of conductive coating slurry for sodium ion battery
By using polycarbonate diol and other materials in sodium ion batteries, the problem of poor water resistance of carbon-coated aluminum foil conductive coating is solved, the cycle life and Coulomb efficiency of the battery are improved, and the battery's plurality is enhanced. Performance and charge and discharge speed.
Patent Information
- Application Number
- CN202411273706.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The conductive coating of carbon-coated aluminum foil for the negative electrode of sodium ion battery has poor water resistance, which leads to unstable interface between the electrolyte and the current collector, increases internal resistance, and reduces the battery cycle life and Coulomb efficiency.
Polyurethane emulsions are prepared by reacting polycarbonate diol, modified monomer, isophorone diisocyanate and other materials, and treated with graphene and KH570 to form modified graphene, increasing the crosslinking site and long-chain fluorane side chain, improves the water resistance of the coating.
It significantly improves the water resistance of the conductive coating, extends the battery's cycle life and Coulomb efficiency, and enhances the battery's rate performance and charge and discharge speed.
Smart Images

Figure BDA0005039483160000111 
Figure BDA0005039483160000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a preparation method and application of a conductive coating slurry for sodium ion batteries. Background Art
[0002] The application of sodium-ion batteries is closely related to the positive and negative electrode materials of the battery, and the performance of the positive and negative electrode materials directly affects the performance of the battery. At present, the negative electrode materials of the battery include carbon-based materials, transition metal oxides and sulfides, alloy materials, etc. Carbon-coated aluminum foil is also a commonly used material for the negative electrode of sodium-ion batteries, but the coating of carbon-coated aluminum foil has poor water resistance, which easily leads to unstable interface between the electrolyte and the current collector. This instability will accelerate the occurrence of interfacial side reactions and increase the internal resistance of the battery, thereby reducing the cycle life and coulomb efficiency of the battery. The coating will react with the electrolyte to form an impedance layer, thereby increasing the internal resistance of the battery and reducing the conductivity, which will affect the rate performance and charge and discharge speed of the battery. Therefore, a coating slurry with good water resistance is needed to solve this problem. Summary of the invention
[0003] The purpose of the present invention is to provide a preparation method and application of a conductive coating slurry for a sodium ion battery, which solves the problem of poor water resistance of the conductive coating slurry in the carbon-coated aluminum foil for the sodium ion negative electrode at the current stage.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a conductive coating slurry for a sodium ion battery comprises the following steps:
[0006] Step A1: polycarbonate diol, modified monomer, isophorone diisocyanate and acetone are uniformly mixed, reacted for 1-2 hours at a speed of 120-150 r / min and a temperature of 80-85° C., castor oil and dibutyltin dilaurate are added, reacted for 2-3 hours, 2,2-bis(hydroxymethyl)propionic acid is added, reacted for 2-3 hours, cooled to 40-50° C., allyl alcohol is added, reacted for 1-2 hours, triethylamine is added for neutralization, deionized water is added, and ether is removed by reduced pressure distillation to obtain a polyurethane emulsion;
[0007] Step A2: dispersing graphene in ethanol, stirring and adding KH570 at a speed of 150-200 r / min and a temperature of 60-70° C., reacting for 3-5 hours to obtain modified graphene, weighing the following raw materials in parts by weight: 100-120 parts of polyurethane emulsion, 15-20 parts of modified graphene, 1-3 parts of benzoin ethyl ether, 3-5 parts of dispersant and 1-2 parts of leveling agent, mixing the raw materials evenly, and storing them away from light to obtain a conductive coating slurry for sodium ion batteries.
[0008] Furthermore, the amount ratio of the polycarbonate diol, modified monomer, isophorone diisocyanate, castor oil, 2,2-bis(hydroxymethyl)propionic acid, acryl alcohol and deionized water described in step A1 is 6mmol:2.5mmol:16mmol:1.5mmol:6mmol:1mmol:80mL, the molecular weight of the polycarbonate diol is 1000, and the amount of dibutyltin dilaurate is 2% by mass of isophorone diisocyanate.
[0009] Further, the amount of KH570 described in step A2 is 1% of the mass of graphene, the dispersant model is one or more of OP-10, BYK-190 or BYK-191 mixed in any proportion, and the leveling agent model is one or more of BYK-306, BYK-310 or BYK-3033 mixed in any proportion.
[0010] Further, the modified monomer is prepared by the following steps:
[0011] Step B1: diethanolamine, benzyl chloroformate, sodium bicarbonate and DMF are mixed, and the reaction is carried out for 2-3 hours at a speed of 120-150 r / min and a temperature of 25-30° C. to obtain intermediate 1; intermediate 1, propylene bromide, sodium hydride and DMF are mixed, and the reaction is carried out for 3-5 hours at a speed of 200-300 r / min and a temperature of 40-50° C. to obtain intermediate 2; intermediate 2, heptadecafluoro-1-iodooctane, copper chloride, monoethanolamine and DMF are uniformly mixed, and the reaction is carried out for 3-5 hours at a speed of 60-80 r / min and a temperature of 80-90° C. to obtain intermediate 3;
[0012] Step B2: The intermediate 3, the palladium carbon catalyst and the dioxane are mixed uniformly, and the reaction is carried out for 3-5 hours at a temperature of 25-30° C. and a hydrogen atmosphere to obtain the intermediate 4; the intermediate 4, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, sodium hydride and DMF are mixed, and the reaction is carried out for 3-5 hours at a speed of 150-200 r / min and a temperature of 30-40° C. to obtain the modifier;
[0013] Step B3: octamethylcyclotetrasiloxane, a modifier, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 150-200 r / min and a temperature of 105-110° C. to obtain a diamine-terminated polysiloxane;
[0014] Step B4: Mix diamine-terminated polysiloxane, carbon disulfide, triethylamine and DMF, introduce nitrogen protection, and react for 6-8 hours at a speed of 120-150 r / min and a temperature of 50-60° C. to obtain modified polysiloxane. Mix the modified polysiloxane, sodium hydroxide, polyethylene glycol 400 and toluene evenly, stir and add sodium hypochlorite at a speed of 120-150 r / min and a temperature of 55-65° C., and react for 2-3 hours to obtain a modified monomer.
[0015] Furthermore, the molar ratio of diethanolamine, benzyl chloroformate and sodium bicarbonate described in step B1 is 1:1:1.1, the molar ratio of intermediate 1, propylene bromide and sodium cyanide is 1:2:2.1, the molar ratio of intermediate 2 and heptadecafluoro-1-iodooctane is 1:2, the amount of cupric chloride used is 2% of the total mass of intermediate 2 and heptadecafluoro-1-iodooctane, and the amount of monoethanolamine used is 1% of the total mass of intermediate 2 and heptadecafluoro-1-iodooctane.
[0016] Further, the mass ratio of the intermediate 3 and the palladium-carbon catalyst described in step B2 is 20:1, the molar ratio of the intermediate 4 and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane is 4:1, and the amount of sodium hydride used is 1% of the sum of the mass of the intermediate 4 and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane.
[0017] Furthermore, the molar ratio of octamethylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane in step B3 is 1.8:0.5:3:2.
[0018] Furthermore, the molar ratio of the alkyl group on the diamine-terminated polysiloxane and carbon disulfide in step B4 is 2:1, the amount of triethylamine used is 3% of the mass of carbon disulfide, and the mass ratio of modified polysiloxane, sodium hydroxide, polyethylene glycol 400 and sodium hypochlorite is 20:1:3:120.
[0019] Beneficial effects of the present invention: A conductive coating slurry for a sodium ion battery prepared by the present invention comprises the following raw materials: polyurethane emulsion, modified graphene, benzoin ethyl ether, a dispersant and a leveling agent. The polyurethane emulsion is reacted with polycarbonate diol, a modified monomer and isophorone diisocyanate, then reacted with castor oil, and then reacted with 2,2-bishydroxymethylpropionic acid to form a polyurethane prepolymer, and finally capped with allyl alcohol. The graphene is treated with KH570 to graft double bonds on the surface to obtain the modified graphene.
[0020] The modified monomer is treated with benzyl chloroformate using diethanolamine as a raw material to form a secondary amine protection to obtain an intermediate 1, and the intermediate 1 is reacted with propylene bromide so that the hydroxyl group on the intermediate 1 reacts with the bromine atom site on the propylene bromide to obtain an intermediate 2, and the 17-fluoro-1-iodooctane is reacted with the intermediate 2 so that the iodine atom site on the 17-fluoro-1-iodooctane reacts with the double bond on the intermediate 2 to obtain an intermediate 3, and the intermediate 3 is deprotected using a palladium-carbon catalyst to obtain an intermediate 4, and the intermediate 4 is reacted with 2,4,6,8-tetramethyl -2,4,6,8-tetravinylcyclotetrasiloxane is subjected to the action of sodium hydride to graft the secondary amine on the intermediate 4 with the double bond on the 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane to obtain a modifier, the octamethylcyclotetrasiloxane and the modifier are ring-opened, and then reacted with 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to obtain a diamine-terminated polysiloxane, and the diamine-terminated polysiloxane is reacted with carbon disulfide to form a carbodiimide structure to obtain a modified monomer.
[0021] After coating, the conductive coating slurry is irradiated with ultraviolet light to cross-link the double bonds in the polyurethane emulsion and the double bonds on the modified graphene, thereby increasing the cross-linking sites and improving the cross-linking density, thereby achieving the effect of improving the water resistance of the coating. The main chain of the modified monomer is a silicone segment, and the side chain contains a long-chain fluorocarbon, which can prevent moisture from entering the interior of the coating and increase water resistance. The modified monomer reacts with isophorone diisocyanate to form a carbodiimide structure, which cooperates with the carbodiimide structure on the polyurethane molecular chain to react with the carboxyl group produced by hydrolysis to achieve a neutralization effect, and repair broken polymer chains to further improve hydrolysis resistance. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1
[0024] A method for preparing a conductive coating slurry for a sodium ion battery comprises the following steps:
[0025] Step A1: polycarbonate diol, modified monomer, isophorone diisocyanate and acetone are uniformly mixed, reacted at a speed of 120 r / min and a temperature of 80° C. for 1 h, castor oil and dibutyltin dilaurate are added, reacted for 2 h, 2,2-bis(hydroxymethyl)propionic acid is added, reacted for 2 h, cooled to 40° C., allyl alcohol is added, reacted for 1 h, triethylamine is added for neutralization, deionized water is added, and ether is removed by reduced pressure distillation to obtain a polyurethane emulsion;
[0026] Step A2: Disperse graphene in ethanol, stir and add KH570 at a speed of 150 r / min and a temperature of 60°C, and react for 3 hours to obtain modified graphene. Weigh the following raw materials in parts by weight: 100 parts of polyurethane emulsion, 15 parts of modified graphene, 1 part of benzoin ethyl ether, 3 parts of dispersant and 1 part of leveling agent, mix the raw materials evenly, and store them away from light to obtain a conductive coating slurry for sodium ion batteries.
[0027] The amount ratio of the polycarbonate diol, modified monomer, isophorone diisocyanate, castor oil, 2,2-bis(hydroxymethyl)propionic acid, acryl alcohol and deionized water described in step A1 is 6mmol:2.5mmol:16mmol:1.5mmol:6mmol:1mmol:80mL, the molecular weight of the polycarbonate diol is 1000, and the amount of dibutyltin dilaurate is 2% by mass of isophorone diisocyanate.
[0028] The amount of KH570 used in step A2 is 1% of the mass of graphene, the model of the dispersant is OP-10, and the model of the leveling agent is BYK-306.
[0029] The modified monomer is prepared by the following steps:
[0030] Step B1: diethanolamine, benzyl chloroformate, sodium bicarbonate and DMF were mixed, and the reaction was carried out at a speed of 120 r / min and a temperature of 25° C. for 2 h to obtain intermediate 1. Intermediate 1, propylene bromide, sodium hydride and DMF were mixed, and the reaction was carried out at a speed of 200 r / min and a temperature of 40° C. for 3 h to obtain intermediate 2. Intermediate 2, heptadecafluoro-1-iodooctane, copper chloride, monoethanolamine and DMF were mixed uniformly, and the reaction was carried out at a speed of 60 r / min and a temperature of 80° C. for 3 h to obtain intermediate 3.
[0031] Step B2: The intermediate 3, the palladium carbon catalyst and the dioxane were mixed evenly, and the reaction was carried out for 3 hours at a temperature of 25° C. and a hydrogen atmosphere to obtain the intermediate 4. The intermediate 4, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, sodium hydride and DMF were mixed, and the reaction was carried out for 3 hours at a speed of 150 r / min and a temperature of 30° C. to obtain the modifier:
[0032] Step B3: octamethylcyclotetrasiloxane, a modifier, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide were uniformly mixed, nitrogen was introduced for protection, and the reaction was carried out at a speed of 150 r / min and a temperature of 105° C. for 3 hours to obtain a diamine-terminated polysiloxane;
[0033] Step B4: Mix diamine-terminated polysiloxane, carbon disulfide, triethylamine and DMF, introduce nitrogen protection, and react for 6 hours at a speed of 120 r / min and a temperature of 50°C to obtain modified polysiloxane. Mix the modified polysiloxane, sodium hydroxide, polyethylene glycol 400 and toluene evenly, stir and add sodium hypochlorite at a speed of 120 r / min and a temperature of 55°C, and react for 2 hours to obtain a modified monomer.
[0034] The molar ratio of diethanolamine, benzyl chloroformate and sodium bicarbonate described in step B1 is 1:1:1.1, the molar ratio of intermediate 1, propylene bromide and sodium cyanide is 1:2:2.1, the molar ratio of intermediate 2 and heptadecafluoro-1-iodooctane is 1:2, the amount of cupric chloride used is 2% of the total mass of intermediate 2 and heptadecafluoro-1-iodooctane, and the amount of monoethanolamine used is 1% of the total mass of intermediate 2 and heptadecafluoro-1-iodooctane.
[0035] The mass ratio of intermediate 3 and palladium-carbon catalyst described in step B2 is 20:1, the molar ratio of intermediate 4 and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane is 4:1, and the amount of sodium hydride is 1% of the mass sum of intermediate 4 and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane.
[0036] The molar ratio of octamethylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane in step B3 is 1.8:0.5:3:2.
[0037] The molar ratio of the alkyl group on the diamine-terminated polysiloxane and carbon disulfide in step B4 is 2:1, the amount of triethylamine used is 3% of the mass of carbon disulfide, and the mass ratio of modified polysiloxane, sodium hydroxide, polyethylene glycol 400 and sodium hypochlorite is 20:1:3:120.
[0038] Example 2
[0039] A method for preparing a conductive coating slurry for a sodium ion battery comprises the following steps:
[0040] Step A1: polycarbonate diol, modified monomer, isophorone diisocyanate and acetone are uniformly mixed, reacted at a speed of 120 r / min and a temperature of 85° C. for 2 h, castor oil and dibutyltin dilaurate are added, reacted for 2 h, 2,2-bis(hydroxymethyl)propionic acid is added, reacted for 3 h, cooled to 45° C., allyl alcohol is added, reacted for 1.5 h, triethylamine is added for neutralization, deionized water is added, and ether is removed by reduced pressure distillation to obtain a polyurethane emulsion;
[0041] Step A2: Disperse graphene in ethanol, stir and add KH570 at a speed of 150 r / min and a temperature of 65°C, and react for 4 hours to obtain modified graphene. Weigh the following raw materials in parts by weight: 110 parts of polyurethane emulsion, 18 parts of modified graphene, 2 parts of benzoin ethyl ether, 4 parts of dispersant and 1.5 parts of leveling agent, mix the raw materials evenly, and store them away from light to obtain a conductive coating slurry for sodium ion batteries.
[0042] The amount ratio of the polycarbonate diol, modified monomer, isophorone diisocyanate, castor oil, 2,2-bis(hydroxymethyl)propionic acid, acryl alcohol and deionized water described in step A1 is 6mmol:2.5mmol:16mmol:1.5mmol:6mmol:1mmol:80mL, the molecular weight of the polycarbonate diol is 1000, and the amount of dibutyltin dilaurate is 2% by mass of isophorone diisocyanate.
[0043] The amount of KH570 used in step A2 is 1% of the mass of graphene, the model of the dispersant is BYK-190, and the model of the leveling agent is BYK-310.
[0044] The modified monomer is prepared by the following steps:
[0045] Step B1: diethanolamine, benzyl chloroformate, sodium bicarbonate and DMF were mixed, and the reaction was carried out at a speed of 120 r / min and a temperature of 30° C. for 2 h to obtain intermediate 1. Intermediate 1, propylene bromide, sodium hydride and DMF were mixed, and the reaction was carried out at a speed of 300 r / min and a temperature of 45° C. for 4 h to obtain intermediate 2. Intermediate 2, heptadecafluoro-1-iodooctane, copper chloride, monoethanolamine and DMF were mixed uniformly, and the reaction was carried out at a speed of 80 r / min and a temperature of 85° C. for 4 h to obtain intermediate 3.
[0046] Step B2: The intermediate 3, the palladium carbon catalyst and the dioxane are mixed uniformly, and the reaction is carried out for 4 hours at a temperature of 28° C. and a hydrogen atmosphere to obtain the intermediate 4. The intermediate 4, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, sodium hydride and DMF are mixed, and the reaction is carried out for 4 hours at a speed of 200 r / min and a temperature of 35° C. to obtain the modifier.
[0047] Step B3: octamethylcyclotetrasiloxane, a modifier, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide were uniformly mixed, nitrogen was introduced for protection, and the reaction was carried out at a speed of 150 r / min and a temperature of 110° C. for 4 hours to obtain a diamine-terminated polysiloxane;
[0048] Step B4: Mix diamine-terminated polysiloxane, carbon disulfide, triethylamine and DMF, introduce nitrogen protection, and react for 7 hours at a speed of 120 r / min and a temperature of 55°C to obtain modified polysiloxane. Mix the modified polysiloxane, sodium hydroxide, polyethylene glycol 400 and toluene evenly, stir and add sodium hypochlorite at a speed of 120 r / min and a temperature of 60°C, and react for 3 hours to obtain a modified monomer.
[0049] The molar ratio of diethanolamine, benzyl chloroformate and sodium bicarbonate described in step B1 is 1:1:1.1, the molar ratio of intermediate 1, propylene bromide and sodium cyanide is 1:2:2.1, the molar ratio of intermediate 2 and heptadecafluoro-1-iodooctane is 1:2, the amount of cupric chloride used is 2% of the total mass of intermediate 2 and heptadecafluoro-1-iodooctane, and the amount of monoethanolamine used is 1% of the total mass of intermediate 2 and heptadecafluoro-1-iodooctane.
[0050] The mass ratio of intermediate 3 and palladium-carbon catalyst described in step B2 is 20:1, the molar ratio of intermediate 4 and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane is 4:1, and the amount of sodium hydride is 1% of the mass sum of intermediate 4 and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane.
[0051] The molar ratio of octamethylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane in step B3 is 1.8:0.5:3:2.
[0052] The molar ratio of the alkyl group on the diamine-terminated polysiloxane and carbon disulfide in step B4 is 2:1, the amount of triethylamine used is 3% of the mass of carbon disulfide, and the mass ratio of modified polysiloxane, sodium hydroxide, polyethylene glycol 400 and sodium hypochlorite is 20:1:3:120.
[0053] Example 3
[0054] A method for preparing a conductive coating slurry for a sodium ion battery comprises the following steps:
[0055] Step A1: polycarbonate diol, modified monomer, isophorone diisocyanate and acetone are uniformly mixed, reacted at a speed of 150 r / min and a temperature of 85° C. for 2 h, castor oil and dibutyltin dilaurate are added, reacted for 3 h, 2,2-bis(hydroxymethyl)propionic acid is added, reacted for 3 h, cooled to 50° C., allyl alcohol is added, reacted for 2 h, triethylamine is added for neutralization, deionized water is added, and ether is removed by reduced pressure distillation to obtain a polyurethane emulsion;
[0056] Step A2: Disperse graphene in ethanol, stir and add KH570 at a speed of 200 r / min and a temperature of 70°C, and react for 5 hours to obtain modified graphene. Weigh the following raw materials in parts by weight: 120 parts of polyurethane emulsion, 20 parts of modified graphene, 3 parts of benzoin ethyl ether, 5 parts of dispersant and 2 parts of leveling agent, mix the raw materials evenly, and store them away from light to obtain a conductive coating slurry for sodium ion batteries.
[0057] The amount ratio of the polycarbonate diol, modified monomer, isophorone diisocyanate, castor oil, 2,2-bis(hydroxymethyl)propionic acid, acryl alcohol and deionized water described in step A1 is 6mmol:2.5mmol:16mmol:1.5mmol:6mmol:1mmol:80mL, the molecular weight of the polycarbonate diol is 1000, and the amount of dibutyltin dilaurate is 2% by mass of isophorone diisocyanate.
[0058] The amount of KH570 used in step A2 is 1% of the mass of graphene. The model of the dispersant is BYK-191, and the model of the leveling agent is BYK-3033.
[0059] The modified monomer is prepared by the following steps:
[0060] Step B1: diethanolamine, benzyl chloroformate, sodium bicarbonate and DMF were mixed, and the reaction was carried out at a speed of 150 r / min and a temperature of 30° C. for 3 h to obtain intermediate 1. Intermediate 1, propylene bromide, sodium hydride and DMF were mixed, and the reaction was carried out at a speed of 300 r / min and a temperature of 50° C. for 5 h to obtain intermediate 2. Intermediate 2, heptadecafluoro-1-iodooctane, copper chloride, monoethanolamine and DMF were mixed uniformly, and the reaction was carried out at a speed of 80 r / min and a temperature of 90° C. for 5 h to obtain intermediate 3.
[0061] Step B2: The intermediate 3, the palladium carbon catalyst and the dioxane were mixed evenly, and the reaction was carried out for 5 hours at a temperature of 30° C. and a hydrogen atmosphere to obtain the intermediate 4. The intermediate 4, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, sodium hydride and DMF were mixed, and the reaction was carried out for 5 hours at a speed of 200 r / min and a temperature of 40° C. to obtain the modifier.
[0062] Step B3: octamethylcyclotetrasiloxane, a modifier, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide were uniformly mixed, nitrogen was introduced for protection, and the reaction was carried out at a speed of 200 r / min and a temperature of 110° C. for 5 hours to obtain a diamine-terminated polysiloxane;
[0063] Step B4: Mix diamine-terminated polysiloxane, carbon disulfide, triethylamine and DMF, introduce nitrogen protection, and react for 8 hours at a speed of 150 r / min and a temperature of 60°C to obtain modified polysiloxane. Mix the modified polysiloxane, sodium hydroxide, polyethylene glycol 400 and toluene evenly, stir and add sodium hypochlorite at a speed of 150 r / min and a temperature of 65°C, and react for 3 hours to obtain a modified monomer.
[0064] The molar ratio of diethanolamine, benzyl chloroformate and sodium bicarbonate described in step B1 is 1:1:1.1, the molar ratio of intermediate 1, propylene bromide and sodium cyanide is 1:2:2.1, the molar ratio of intermediate 2 and heptadecafluoro-1-iodooctane is 1:2, the amount of cupric chloride used is 2% of the total mass of intermediate 2 and heptadecafluoro-1-iodooctane, and the amount of monoethanolamine used is 1% of the total mass of intermediate 2 and heptadecafluoro-1-iodooctane.
[0065] The mass ratio of intermediate 3 and palladium-carbon catalyst described in step B2 is 20:1, the molar ratio of intermediate 4 and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane is 4:1, and the amount of sodium hydride is 1% of the mass sum of intermediate 4 and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane.
[0066] The molar ratio of octamethylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane in step B3 is 1.8:0.5:3:2.
[0067] The molar ratio of the alkyl group on the diamine-terminated polysiloxane and carbon disulfide in step B4 is 2:1, the amount of triethylamine used is 3% of the mass of carbon disulfide, and the mass ratio of modified polysiloxane, sodium hydroxide, polyethylene glycol 400 and sodium hypochlorite is 20:1:3:120.
[0068] Comparative Example 1
[0069] Compared with Example 1, this comparative example uses graphene instead of modified graphene, and the remaining steps are the same.
[0070] Comparative Example 2
[0071] Compared with Example 1, castor oil was not added in this comparative example, and the remaining steps were the same.
[0072] Comparative Example 3
[0073] Compared with Example 1, no propenol was added in this comparative example, and the remaining steps were the same.
[0074] Comparative Example 4
[0075] Compared with Example 1, no modifier was added in this comparative example, and the remaining steps were the same.
[0076] Comparative Example 5
[0077] Compared with Example 1, this comparative example uses diamine-terminated polysiloxane instead of the modified monomer, and the remaining steps are the same.
[0078] The conductive coating slurries prepared in Examples 1-3 and Comparative Examples 1-5 were tested according to the standard of GB / T1733-1993, immersed for 24 hours, 48 hours and 120 hours, and the state of the paint film was observed. The test results are shown in the following table.
[0079]
[0080]
[0081] It can be seen from the above table that this application has a very good water resistance effect.
[0082] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a conductive coating slurry for a sodium ion battery, characterized in that: The specific steps include: Step A1: polycarbonate diol, modified monomer, isophorone diisocyanate and acetone are mixed for reaction, castor oil and dibutyltin dilaurate are added, 2,2-bis(hydroxymethyl)propionic acid is added, reaction is carried out, cooling is performed, allyl alcohol is added, reaction is carried out, triethylamine is added for neutralization, deionized water is added, and ether is removed by reduced pressure distillation to obtain a polyurethane emulsion; Step A2: Disperse graphene in ethanol, stir and add KH570 to react to obtain modified graphene, weigh the following raw materials in parts by weight: 100-120 parts of polyurethane emulsion, 15-20 parts of modified graphene, 1-3 parts of benzoin ethyl ether, 3-5 parts of dispersant and 1-2 parts of leveling agent, mix the raw materials evenly, and store them away from light to obtain a conductive coating slurry for sodium ion batteries.
2. The method for preparing a conductive coating slurry for a sodium ion battery according to claim 1, characterized in that: The amount ratio of the polycarbonate diol, modified monomer, isophorone diisocyanate, castor oil, 2,2-bis(hydroxymethyl)propionic acid, allyl alcohol and deionized water described in step A1 is 6 mmol: 2.5 mmol: 16 mmol: 1.5 mmol: 6 mmol: 1 mmol: 80 mL.
3. The method for preparing a conductive coating slurry for a sodium ion battery according to claim 1, characterized in that: The amount of KH570 used in step A2 is 1% of the mass of graphene.
4. The method for preparing a conductive coating slurry for a sodium ion battery according to claim 1, characterized in that: The modified monomer is prepared by the following steps: Step B1: diethanolamine, benzyl chloroformate, sodium bicarbonate and DMF are mixed to react to obtain intermediate 1, intermediate 1, propylene bromide, sodium hydride and DMF are mixed to react to obtain intermediate 2, intermediate 2, heptadecafluoro-1-iodooctane, copper chloride, monoethanolamine and DMF are mixed to react to obtain intermediate 3, Step B2: The intermediate 3, the palladium carbon catalyst and the dioxane are uniformly mixed, and the mixture is reacted at a temperature of 25-30° C. in a hydrogen atmosphere to obtain the intermediate 4. The intermediate 4, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, sodium hydride and DMF are mixed and reacted to obtain the modifier; Step B3: octamethylcyclotetrasiloxane, a modifier, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and a reaction is carried out to obtain a diamine-terminated polysiloxane; Step B4: diamine-terminated polysiloxane, carbon disulfide, triethylamine and DMF are mixed, nitrogen is introduced for protection, and a reaction is carried out to obtain a modified polysiloxane; the modified polysiloxane, sodium hydroxide, polyethylene glycol 400 and toluene are evenly mixed, stirred and sodium hypochlorite is added, and a reaction is carried out to obtain a modified monomer.
5. The method for preparing a conductive coating slurry for a sodium ion battery according to claim 4, characterized in that: The molar ratio of diethanolamine, benzyl chloroformate and sodium bicarbonate in step B1 is 1:1:1.1, the molar ratio of intermediate 1, propylene bromide and sodium cyanide is 1:2:2.1, and the molar ratio of intermediate 2 and heptadecafluoro-1-iodooctane is 1:
2.
6. The method for preparing a conductive coating slurry for a sodium ion battery according to claim 4, characterized in that: The mass ratio of the intermediate 3 and the palladium-carbon catalyst described in step B2 is 20:1, and the molar ratio of the intermediate 4 and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane is 4:
1.
7. The method for preparing a conductive coating slurry for a sodium ion battery according to claim 4, characterized in that: The molar ratio of octamethylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B3 is 1.8:0.5:3:
2.
8. The method for preparing a conductive coating slurry for a sodium ion battery according to claim 4, characterized in that: The molar ratio of the alkyl group on the diamine-terminated polysiloxane and carbon disulfide in step B4 is 2:1, and the mass ratio of the modified polysiloxane, sodium hydroxide, polyethylene glycol 400 and sodium hypochlorite is 20:1:3:
120.
9. Use of the conductive coating slurry according to any one of claims 1 to 8 in carbon-coated aluminum foil for sodium ion batteries.
Citation Information
Patent Citations
Process for reacting a perfluoroalkyl iodide with an olefinic compound
CA2152980A1
Graphene-modified waterborne polyurethane anticorrosion coating and preparation method thereof
CN110499094A
Preparation method and application of bacteriostatic waterborne polyurethane emulsion
CN116622051A
Non-dull waterborne polyurethane finish paint and preparation method thereof
CN117247733A
Process for reacting a perfluoroalkl iodide with an olefinic compound
US5585517A
